KEGIATAN MAIN UNTUK MENGEMBANGKAN KOGNITIF ANAK DI TK HARAPAN BUNDA KABUPATEN ACEH SELATAN - Tuti Mahendri; Yuhasriati .; Rosmiati .; Suhartati .; Khoiriyah . (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2023)
Keywords: Play activities, Cognitive ability, Child response, Early childhoodEarly age is the development of a golden age that has meaning for children's lives, because at this time all aspects of development are developing very rapidly, especially children's cognitive abilities. One strategy to improve children's cognitive abilities is to play. Play is defined as an exercise to connect various kinds of knowledge and cognitive skills that are just realized, so that they can function regularly. The purpose of the study was to determine play activities to develop children's cognitive abilities in Harapan Bunda Kindergarten, South Aceh Regency and to determine children's responses to play activities carried out by teachers to develop children's cognitive at Harapan Bunda Kindergarten, South Aceh Regency. This study uses a qualitative approach with a descriptive type of research. Data collection techniques in the form of observation and interviews. The research subjects were class B children (20 students) and homeroom teachers for class B (1 person). The object of this research is play activities to develop children's cognitive abilities in Harapan Bunda Kindergarten, South Aceh Regency and children's responses to play activities carried out by teachers to develop children's cognitive at Harapan Bunda Kindergarten, South Aceh Regency. The results showed that playing activities to develop children's cognitive abilities in Harapan Bunda Kindergarten, South Aceh Regency were using loose parts. The play activities carried out were arranging balloons, comparing their sizes, presenting balloon shapes, mentioning colors, matching objects, and taking the initiative. Children's responses to play activities carried out by teachers to develop children's cognitive at Harapan Bunda Kindergarten, South Aceh Regency are able to recognize objects according to size, shape, color, be able to recognize objects according to their function/use and also be able to solve problems in playing activities.Abstrak. Usia dini merupakan perkembangan usia emas yang sangat memiliki makna bagi kehidupan anak, karena pada masa ini seluruh aspek perkembangan berkembang dengan sangat pesat, terutama kemampuan kognitif anak. Salah satu strategi untuk meningkatkan kemampuan kognitif anak yaitu dengan bermain. Bermain diartikan sebagai latihan untuk menghubungkan macam-macam pengetahuan dan keterampilan kognitif yang baru disadari, sehingga bisa berfungsi secara teratur. Tujuan penelitian untuk mengetahui kegiatan main untuk mengembangkan kemampuan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan dan mengetahui respon anak terhadap kegiatan main yang dilakukan guru untuk mengembangkan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data berupa observasi dan wawancara. Subjek penelitian adalah anak kelas B (20 anak didik) serta guru wali kelas B (1 orang). Objek penelitian ini adalah kegiatan main untuk mengembangkan kemampuan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan dan respon anak terhadap kegiatan main yang dilakukan guru untuk mengembangkan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan. Hasil penelitian menunjukkan bahwa kegiatan main untuk mengembangkan kemampuan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan adalah menggunakan loose Part (lepas/bebas). Kegiatan main yang dilakukan adalah menata balon, membandingkan ukurannya, mempersentasikan bentuk balon, menyebutkan warna, mencocokan benda, dan berinisiatif. respon anak terhadap kegiatan main yang dilakukan guru untuk mengembangkan kognitif anak di TK Harapan Bunda Kabupaten Aceh Selatan adalah mampu mengenal benda sesuai dengan ukuran, bentuk, warna, mampu mengenal benda sesuai fungsi/kegunaannya dan juga mampu menyelesaikan masalah dalam melakukan kegiatan main.Kata Kunci: Kegiatan main, Kemampuan kognitif, Respon anak, Anak usia dini